Plan de negocios para la creación de una empresa automatizada de papelería con horarios extendidos en la ciudad de Quito - Cárdenas Vega, Natasha Daniela (2020)
The objective of this thesis is to analyze the feasibility of the creation of an automated stationery company with extended hours in the city of Quito; which allows customers to have a different experience, through an automated system that provides speed and comfort, without the need for customers to leave their own car. An analysis has been carried out in different perspectives such as: country situation, competitors, administrative, operational, commercial and financial area; and in the same way the knowledge acquired throughout the undergraduate degree has been used. All these perspectives have allowed to determine the viability and sustainability of the project. The external analysis (PEST and Porter), the analysis of the client through qualitative and quantitative research, the marketing plan that allows to determine the appropriate strategies to enter the market, the organizational structure together with the mission, vision and objectives that allows to determine the internal and external processes, the value proposition of the company, the financial evaluation that consists of the projection of income, costs, expenses, and others. Finally, the establishment of financial policies and indicators, have allowed to determine if the project is feasible, profitable, viable and sustainable within a period of five years. Once all these aspects have been analyzed and evaluated, it can be concluded that the project is viable, with a profitability index of 1,37 for the project and 2,04 for the investor. Similarly, the project has an internal rate of return of 43,9 percent which is higher than the expected rate of return.